Affective Neuroscience Contributions to the Treatment of Addiction: The Role of Social Instincts, Pleasure and SEEKING - Flores Mosri, Daniela (Frontiers in Psychiatry, 2021)
Addiction is an illness with multiple health risks that continues to be prevalent in worldwide population. Because of the nature of addictive disorders, users of drugs seldom look for treatment and when they do, availability can be of restricted access. Permanence in treatment and its outcomes vary from case to case. Most models keep a multidisciplinary approach that tackles several dimensions of addictive disorders. However, the different etiological factors involved claim for a personalized treatment to enhance opportunities for better results. It has been recognized that problems in relationships with others play an important role in the etiology and in the recovery process of addiction. This paper focuses on the social environmental causes of addiction based on an affective neuroscience approach that attempts to integrate the interplay between social instincts, pleasure, and the SEEKING system in addiction. To advance towards better treatment strategies, it is pertinent to understand the limitations of the current multidisciplinary models. Acknowledging the social nature of the human brain may help to identify the quality of different types of traumatic early-life experiences in drug users and how to address them in what may constitute a neuropsychoanalytic treatment of addiction.